Analisis Efektivitas Sistem Informasi Akuntansi dalam Verifikasi Biaya Ongkos Angkut di Salah Satu Perusahaan BUMN - Fatikhin, Bahrul; Sofie Yunida Putri (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to analyze the implementation of an Accounting Information System (AIS) in the form of a Contractor Safety Management System (CSMS) in the freight cost verification process at a state-owned enterprise (SOE) operating in the cement manufacturing sector. The study employs a descriptive qualitative approach, with data collected through observations and interviews conducted during an internship program. The informants include a Freight Cost Verification Specialist, a Verification Lead, and a Verification Manager who are directly involved in the verification process. The findings indicate that the implementation of CSMS as part of the AIS improves verification efficiency, data accuracy and validity, as well as transparency and internal control through integrated and real-time process documentation. However, several limitations are also identified, including system performance constraints during peak transaction periods, dependency on system and network stability, and insufficient optimization of human resources and system infrastructure. These findings suggest that the effectiveness of AIS implementation depends not only on system capabilities but also on organizational readiness and operational support in enhancing freight cost verification processes.